Pemanfaatan Hydrilla verticillata untuk Menurunkan Konsentrasi Cu2+ pada Air Limbah Pelapisan Logam melalui Variasi Berat Tumbuhan - Izzah, Nuril; Amalia, Aussie; Syadzadhiya Qothrunada Zakiyayasin Nisa' (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Liquid waste from metal-plating industries is known to contain copper (Cu²⁺), which is toxic to living organisms if not properly treated. Hydrilla verticillata is an invasive aquatic plant capable of rapid growth and heavy metal accumulation, making it a potential candidate for use in wastewater treatment through phytoremediation. This study aims to analyze the effect of the weight of Hydrilla verticillata on the reduction of Cu²⁺ concentration in metal-plating wastewater. The wastewater used in this study was effluent that had undergone preliminary treatment with the addition of lime and NaHCO₃. The experiments were carried out in a 5-liter laboratory reactor for 15 days, including a 5-day acclimatization period and a 7-day initial toxicity test (Range Finding Test). The weight variations of Hydrilla verticillata used were 75 g, 100 g, and 125 g. The results showed that Hydrilla verticillata was able to reduce Cu2+ concentration by up to 99.05% at a weight of 125 g within 15 days. This indicates that the weight of Hydrilla verticillata significantly influences the reduction of copper (Cu2+) in metal-plating industrial wastewater.